If f(x) = -x + 5 and g(x) = 3x + 2, Find f(2)*g(2).

Question

If f(x) = -x + 5 and g(x) = 3x + 2, Find f(2)*g(2).

in progress 0
Calantha 2 months 2021-08-02T18:56:39+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-02T18:58:03+00:00

    Answer:

    24

    Step-by-step explanation:

    To find f(#) or g(#), plug the number into each x of the equation.

    f(x) = -x + 5

    f(2) = -(2) + 5

    Simplify the parentheses by multiplying.

    f(2) = -2 + 5

    Add.

    f(2) = 3

    g(x) = 3x + 2

    g(2) = 3(2) + 2

    Simplify the parentheses by multiplying.

    g(2) = 6 + 2

    Add.

    g(2) = 8

    Now they are asking you to multiply

    f(2) • g(2)

    3 • 8

    = 24

    Hope this helps!

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )